Sb2Se3 films fabricated by thermal evaporation and post annealing. (January 2021) - Zhang, Leng; Wu, Kongping; Yu, Jing; Yu, Yongyi; Wei, Yaowei
Abstract: Herein, Sb2 Se3 -related thin films were prepared by thermal evaporation at room-temperature and post annealing at high temperature. The Sb2 Se3 film performance was studied as a function of annealing atmosphere: an inert Ar atmosphere, a H2 S-containing atmosphere or a H2 Se-containing atmosphere. The phase structure and microscopic morphology were mainly investigated as a function of temperature and annealing atmosphere. The results show that all films possess the orthorhombic Sb2 Se3 phase regardless of the annealing atmosphere. Furthermore, the preferred epitaxial growth of the films annealed under the H2 S-containing and H2 Se-containing atmospheres is along (020) and (120) planes; while the preferred epitaxial growth of the films annealed under an inert Ar atmosphere is along (211) and (221) planes. When subjecting the films to annealing temperatures >450 °C, the film thickness was observed to reduce when annealing under Ar and H2 Se-containing atmospheres, which may be ascribed to the volatilization of the films at high temperatures. Highlights: All of the three post annealing can facilitate Sb2 Se3 precursor to form orthorhombic Sb2 Se3 phase. The film annealed at inert argon atmosphere possesses preferred orientation of (211) and (221) plane. The annealing temperature should not exceed 450 °C to ensure sufficient Sb2 Se3 film thickness.